2019
DOI: 10.1093/nar/gky1317
|View full text |Cite
|
Sign up to set email alerts
|

Histone demethylase KDM3A is required for enhancer activation of hippo target genes in colorectal cancer

Abstract: Hippo pathway is involved in tumorigenesis, and its regulation in cytosol has been extensively studied, but its regulatory mechanisms in the nuclear are not clear. In the current study, using a FBS-inducing model following serum starvation, we identified KDM3A, a demethylase of histone H3K9me1/2, as a positive regulator for hippo target genes. KDM3A promotes gene expression through two mechanisms, one is to upregulate YAP1 expression, and the other is to facilitate H3K27ac on the enhancers of hippo target gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 47 publications
0
53
0
Order By: Relevance
“…As prior work veri ed, M2 macrophage can be induced by KDM3A [21]. Additionally, it is addressed that KDM3A, a demethylase of histone H3K9me1/2, can promote the expression of CTGF by facilitating H3K27ac on the enhancers of CTGF [22]. While CTGF promotes drug-resistance in glioblastoma cells and facilitates the progression of glioblastoma [23].…”
Section: Discussionmentioning
confidence: 96%
“…As prior work veri ed, M2 macrophage can be induced by KDM3A [21]. Additionally, it is addressed that KDM3A, a demethylase of histone H3K9me1/2, can promote the expression of CTGF by facilitating H3K27ac on the enhancers of CTGF [22]. While CTGF promotes drug-resistance in glioblastoma cells and facilitates the progression of glioblastoma [23].…”
Section: Discussionmentioning
confidence: 96%
“…Increasing evidence has shown that JMJD1A promotes proliferation, survival, and metastasis in several types of cancers, including prostate cancer, colorectal cancer, hepatocellular carcinoma, ovarian cancer, bladder cancer, and Ewing sarcoma 14‐20,31‐34 . Moreover, it has been reported that JMJD1A is downregulated in nasopharyngeal carcinoma (NPC) and downregulation of JMJD1A is associated with poor prognosis of NPC patients 35 .…”
Section: Discussionmentioning
confidence: 99%
“…JMJD1A plays crucial roles in various cellular processes, including spermatogenesis, 7 energy metabolism, 8,9 sex determination, 10 stem cell self‐renewal, 11,12 and differentiation 13 . JMJD1A is shown to play a tumor‐promoting role in several types of cancers, such as colorectal cancer, prostate cancer, hepatocellular carcinoma, ovarian cancer, and bladder cancer 14‐20 . Although JMJD1A has been shown to be a predictor for prognosis and a potential therapeutic target for GC, 21 the role and the underlying mechanism of JMJD1A in GC progression remain to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…5C, S9). Since heterochromatin that is characterized by H3K9me2 and binding of HP1γ is also associated with a histone de-acetylation on H3K27 (Naruse et al, 2020) (Wang et al, 2019), we sought to investigate whether inhibiting the deacetylation of histones in oocytes will cause a similar effect. Previous reports also showed that treatment with a histone deacetylase (HDAC) inhibitor affects oocyte maturation in-vitro (Jin et al, 2014).…”
Section: Resultsmentioning
confidence: 99%